Enhancing SOE Performance in Indonesia: The Role of Governance and Internal Control - Alipudin, Asep; Rahmi, Amelia (International Journal of Social Science and Business, 2025)
State-Owned Enterprises (SOEs) in Indonesia play a crucial role in the nation's economic development. While some SOEs have achieved significant profitability and operational efficiency, others face challenges such as governance issues and financial inefficiencies. This study examines the impact of corporate governance and internal control systems on the performance of SOEs, focusing on both financial and non-financial outcomes. Data were collected through surveys distributed to top management across 29 SOEs, with a total of 290 responses. The results suggest that both corporate governance and internal controls positively influence firm performance, with corporate governance having a slightly stronger impact. This finding emphasizes the importance of transparent and accountable governance structures in achieving long-term sustainability and operational effectiveness. The study also highlights the role of internal controls in mitigating risks, improving efficiency, and ensuring regulatory compliance to improve SOEs’ performance. The research underscores the need for continuous enhancement of both corporate governance and internal control frameworks to improve SOE performance. The findings offer a better understanding of how these systems may interact to influence performance and provide insights that could inform future reforms aimed at strengthening SOEs in Indonesia. Future research should further explore the dynamic relationship between these governance factors and other organizational elements to offer a comprehensive understanding of SOE performance.